Role of Sit-Tight Syndrome in Undermining Democratic Institutions in Nigeria: A Governance Perspective - Olaoye Olumuyiwa Joseph; Joshua Kayode Okunade (Britain International for Academic Research (BIAR) Publisher, 2026)
This research paper investigates the role of the